2007
DOI: 10.1016/j.bbrc.2007.10.037
|View full text |Cite
|
Sign up to set email alerts
|

A nucleosome positioned by α2/Mcm1 prevents Hap1 activator binding in vivo

Abstract: Nucleosome positioning has been proposed as a mechanism of transcriptional repression. Here, we examined whether nucleosome positioning affects activator binding in living yeast cells. We introduced the cognate Hap1 binding site (UAS1) at a location 24-43 bp, 29-48 bp or 61-80 bp interior to the edge of a nucleosome positioned by α2/Mcm1 in yeast minichromosomes. Hap1 binding to the UAS1 was severely inhibited, not only at the pseudo-dyad but also in the peripheral region of the positioned nucleosome in α cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…TFBS localization in NDR is generally believed to be important in enhancing transcription factor binding and facilitating subsequent transcription based on several lines of evidence. Studies on many different factors suggested that nucleosomes limit their TFBS accessibility both in vitro (for review, see Owen-Hughes and Workman, 1994) and in vivo (Liu et al, 2006; Morohashi et al, 2007; Sekinger et al, 2005). Well-studied promoters, such as GAL1-10pr and PHO5pr , have their major TFBS positioned within constitutive NDR, regardless of the transcriptional status of the gene (Lohr, 1997; Svaren and Horz, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…TFBS localization in NDR is generally believed to be important in enhancing transcription factor binding and facilitating subsequent transcription based on several lines of evidence. Studies on many different factors suggested that nucleosomes limit their TFBS accessibility both in vitro (for review, see Owen-Hughes and Workman, 1994) and in vivo (Liu et al, 2006; Morohashi et al, 2007; Sekinger et al, 2005). Well-studied promoters, such as GAL1-10pr and PHO5pr , have their major TFBS positioned within constitutive NDR, regardless of the transcriptional status of the gene (Lohr, 1997; Svaren and Horz, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Second, Cyc8-Tup1 can interact with multiple histone deacetylases in certain in vitro conditions (Watson et al 2000;Wu et al 2001;Davie et al 2003), and it has been proposed that repression is mediated by recruitment of the Hda1 histone deacetylase complex to target promoters (Wu et al 2001;Robyr et al 2002). Third, Tup1 interacts with hypoacetylated tails of histones H3 and H4 (Cooper et al 1994;Edmondson et al 1996;Huang et al 1997) and appears to influence deposition of the Htz1 histone variant (Green and Johnson 2004;Gligoris et al 2007;Morohashi et al 2007). Fourth, Tup1 appears to stabilize nucleosome positioning, perhaps through the Isw2 nucleosome remodeling complex, although Tup1 and Isw2 independently associate with promoters (Zhang and Reese 2004b;Rizzo et al 2011).…”
mentioning
confidence: 99%
“…2B, in good agreement with previous reports. 19,20,22,23,28,30) It is noteworthy that the tentatively assigned nucleosome between nucleosomes V and VI in the previous MNase mapping experiments (white dotted ellipse between lanes 4 and 5 in Fig. 2B) was absent in the H4 S47C-site directed chemical mapping experiments.…”
Section: Resultsmentioning
confidence: 75%
“…The TALS plasmid was constructed by Roth et al 19) TALS was inserted into the Hin-dIII site of a pBR322 derivative to manipulate plasmid construction in Escherichia coli, to form the TALS-pBR322ΔRI plasmid. 22) To eliminate the pUC19 DNA sequence from TALS, the 358 bp region between the two EcoRI sites was replaced by the 378 bp fragment containing the upstream sequence of STE6 (−457 to −83, the translation start site of the gene is defined as +1), forming spTALS1-pBR322ΔRI (spTALS is designated from superior-positioning-TALS). The spTALS2-pBR322ΔRI plasmid was constructed by inverse PCR, using spTALS1-pBR322ΔRI as the template and primers attached to the STE6 upstream sequences at the 5′-end, to extend the STE6 region from −83 to −66.…”
Section: Plasmids and Yeast Strainsmentioning
confidence: 99%
See 1 more Smart Citation